ANALISA PERILAKU ORANG TUA DALAM MERAWAT ANAK SAKIT DI RUMAH SELAMA MASA PANDEMI DI PROVINSI RIAU - dwi elka fitri; Awaliyah Ulfah Ayudytha Ezdha (LPPM Universitas Abdurrab, 2022)
Caring for a sick child is one of the biggest challenges for parents, because they have to deal with the physical, medical and emotional needs of a child that often cannot be controlled when sick. Moreover, the incidence of sick children occurs during the COVID-19 pandemic. During this Covid-19 pandemic, parents are required to be able to take care of sick children at home. This is done to avoid the child being exposed to the virus if taken to the hospital. The purpose of this study was to determine the behavior analysis of parents in caring for sick children at home during the pandemic in Riau Province. The behavior of mothers in caring for sick children at home in this study was divided into 3 parts, namely knowledge, attitudes and actions. This study uses a descriptive statistical research design. The sample in this research is mothers who have children in Marpoyan Damai District, totaling 175 people. The results of this study are sufficient knowledge about caring for sick children at home, as many as 49.4% of mothers, positive attitudes in caring for sick children at home, which is 52.9% of mothers. And 67,2% mothers' actions in caring for sick children at home are not good. It is hoped that from the results of this study, parents (mothers) can provide good actions in caring for sick children during the pandemic. Health workers are also expected to be more aggressive in providing information that can increase knowledge, so that attitudes and actions are also getting better.